Designing anisotropy with waveguide subwavelength structures - Herrero-Bermello, Alaine; Velasco, Aitor V.; Schmid, Jens H.; Cheben, Pavel; Halir, Robert; Luque-González, José Manuel; Ortega-Moñux, Alejandro; Wanguemert-Pérez, Juan Gonzalo; Molina-Fernández, Íñigo (My University, 2018)
Silicon sub-wavelength structures have become a versatile design tool for practical, high-performance integrated optical devices, ranging from highly efficient grating couplers to ultra-broadband beam-splitters. Recently, some of the basic anisotropic properties of these structures have been proposed for advance device design. Here we explore these properties in detail, from the underlying physics to emerging applications in on-chip polarization management.
Keywords: Telecomunicaciones - Congresos; Subwavelength gratings; Anisotropy; Homogenization; Polarization management